2020
DOI: 10.3390/insects11080525
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Pollinating Butterflies in Yunnan Province, Southwest China with Resource Conservation Implications

Abstract: Pollinating butterflies are an important asset to agriculture, which still depends on wild resources. Yunnan Province in Southwest China is a region with typical montane agriculture, but this resource is poorly investigated. From literature reference and specimen examination, the present study identified 554 species of pollinating butterflies (50.8% of the total butterflies) from Yunnan, with family Nymphalidae possessing the least number of pollinators (80 species, 16.0%), while the remaining four families ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The dramatic differences in elevation and microclimate result in a variety of ecosystems, from tropical savannas along the Indian border to subtropical broad leaf and coniferous forests in the Hilly region and to temperate broadleaf and coniferous forests on the lap of the Himalayas (MoFE, 2018; Tripathi et al., 2020). Indeed, previous work in mountainous areas has shown that topological complexity promotes high species richness (Zhang et al., 2020). Nepal provides another example, as its land area occupies just 0.1% of global area, but it contains 3.2% of the world’s floral diversity and 1.1% of global faunal diversity (MFSC, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dramatic differences in elevation and microclimate result in a variety of ecosystems, from tropical savannas along the Indian border to subtropical broad leaf and coniferous forests in the Hilly region and to temperate broadleaf and coniferous forests on the lap of the Himalayas (MoFE, 2018; Tripathi et al., 2020). Indeed, previous work in mountainous areas has shown that topological complexity promotes high species richness (Zhang et al., 2020). Nepal provides another example, as its land area occupies just 0.1% of global area, but it contains 3.2% of the world’s floral diversity and 1.1% of global faunal diversity (MFSC, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While there have been many studies on butterflies from different parts of Nepal (in the Central Himalayan region) (Bhusal & Khanal, 2008; Khanal, 2006; Khanal et al., 2013, 2014; Rai, 2017; Smith & Majupuria, 2006; Suwal et al., 2019), previous studies have focused on the diversity, taxonomy, and distribution of butterflies, and few studies have examined butterfly‐plant interactions (Nepali et al., 2018; Shrestha et al., 2020). However, extensive ecological studies to determine the factors that influence butterfly foraging choices are crucial to improve the ecological utility of butterflies and to preserve them as indicator taxa (Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Areas of high endemism should also be a future priority; the commonly applied parsimony analysis of endemicity affiliated with GIS could provide such vital information for conservation planning [111][112][113][114]. Recent research revealing the spatial character of pollinating butterflies in Yunnan could be a starting point [115].…”
Section: Identify High Priority Areas and Refugiamentioning
confidence: 99%
“…It has been demonstrated that changes in land use management (e.g., increasing landscape heterogeneity, control of alien plant species, introduction of butterfly attracting plants, maintenance of unmanaged hedges, decreased use of PPPs/organic farming, etc.) can solve the dilemma and increase the diversity, abundance, and ecological service functions of butterflies in agroecosystems worldwide [115,[148][149][150][151][152][153][154][155][156].…”
Section: Using Umbrella Species To Boost Conservationmentioning
confidence: 99%
“…In the Himalayan ecosystem of North-East India, settling moths were found to be the vital component of pollination (Singh et al, 2022). In the Yunnan Province of Southwest China, the researchers identified 554 species of pollinating butterflies, and their potential pollinating service could be a great contribution to montane agriculture, which has expanding areas of cash crops and fruit horticulture (Zhang et al, 2020). Except the above spatial research, the temporal research showed that the adult Lepidoptera were often complementary to the diurnal pollinators (Singh et al, 2022; Souza et al, 2022).…”
Section: Introductionmentioning
confidence: 99%